Harta Gono Gini: Analisis Pemahaman Masyarakat Gen Z dan Millenial - Soleh, Muhammad (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2024)
This research examines the perception of Generation Z and Millennials regarding marital joint property (harta gono-gini), a crucial issue in Indonesian marriage law. Using a combination of qualitative and quantitative methods, this study seeks to uncover how these two generations view the division of joint assets after divorce. The results show that Gen Z and Millennials tend to prioritize fair and equitable distribution based on individual contributions during the marriage. However, differences emerge between the two generations in terms of approaches to conflict resolution, where Millennials are more likely to choose mediation, while Gen Z tends to prefer negotiation as a resolution strategy. Furthermore, the study finds that gender also plays a role in shaping perceptions of joint property, with men generally favoring individual ownership, while women emphasize joint ownership and fair division. This research contributes to a better understanding of generational and gender differences in views on joint property in marriage. It also has practical implications for legal practitioners and policymakers in developing more effective conflict resolution frameworks related to marital joint property.